Defining a fish bio-assessment tool to monitoring the biological condition of a cascade reservoirs system in tropical area - Petesse, Maria Letizia [UNESP]; Petrere, Miguel; Agostinho, Angelo Antonio (Elsevier B.V., 2014)
We studied five tropical reservoirs in the cascade system of the Tiete River (State of Sao Paulo, Brazil) in order evaluate the suitability of a fish multimetric index (Reservoir Fish Assemblage Index-RFAI) as a bio-assessment tool. For this purpose, we investigated the spatial and temporal variability of the RFAI with the objectives of testing the effects of the unit measure (catch in numbers or individual weight) of abundance and trophic metrics categories on the index response and, to identify the best sampling season for a bio-assessment program. We located seventy-two sampling sites in three different reservoir zones( fluvial, transition, and lacustrine) and collected samples by habitats -lateral (L), tributary mouth (M) and central (C) - inside each reservoir zone. We recorded the fish assemblages and several physicochemical and habitat variables in the dry and rainy seasons. We tested candidate metrics for range, responsiveness, and redundancy and selected nine for inclusion in the final indices (RFAI(N), the index calculated when we expressed fish in number of individuals, per species, and RFAI(W), calculated when we expressed fishes in weight, per species). We used a discrete scoring criterion (1,3,5), and the final indices varied from 9 to 45. RFAI(N) and RFAI(W) were highly correlated and able to detect a clear spatial variability among the five reservoirs. RFAI(N) showed a higher temporal variability especially in the smaller reservoirs of the system (Bariri, Ibitinga and Nova Avanhandava), allowing us to consider the dry season as the preferable sampling period for the development of bio-assessment programs. RFAI(W) appeared to be more responsive than RFAIN, and was in agreement with the environmental gradients observed when analyzing the physico chemical and habitat variables collected in the present study. These findings indicate that the fish multimetric approach is a suitable tool for the assessment of the biological conditions of these reservoirs. (C) 2014 Elsevier B. V. All rights reserved.
Keywords: Fish multimetric index; Cascade reservoirs system; Tropical environment; Brazil